Dinamika Ilmu Kalam Sunni - Ulum, Bahrul (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2016)
Until recently there were pros and cons about Kalam Science. Some say this science does not need to be studied, while others say it is necessary. Of course to put the issue needs an in-depth study of this science. about this science. Starting from its history to its benefits. Furthermore, fierce debates between scholars and theologians arise from differences in theological figures arose due to differences in addressing the attributes of God. In addition, the entry of non-Islamic philosophical values, especially from Greece. especially from Greece. In its development, the Assyrian school of thought became the most widely embraced school of Muslims traditionally and traditionally in the Islamic world. traditional and hereditary in the Islamic world. Its distinctive feature is that assessment of this science is based on scientific studies not because of like or dislike